Citron kinase is an essential effector of the Pbl-activated Rho signalling pathway in Drosophila melanogaster. - Shandala, T.; Gregory, S.L.; Dalton, H.E.; Smallhorn, M.; Saint, R. (Development, 2004)
Pebble (Pbl)-activated RhoA signalling is essential for cytokinesis in Drosophila melanogaster. Here we report that the Drosophila citron gene encodes an essential effector kinase of Pbl-RhoA signalling in vivo. Drosophila citron is expressed in proliferating tissues but is downregulated in differentiating tissues. We find that Citron can bind RhoA and that localisation of Citron to the contractile ring is dependent on the cytokinesis-specific Pbl-RhoA signalling. Phenotypic analysis of mutants showed that citron is required for cytokinesis in every tissue examined, with mutant cells exhibiting multinucleate and hyperploid phenotypes. Strong genetic interactions were observed between citron and pbl alleles and constructs. Vertebrate studies implicate at least two Rho effector kinases, Citron and Rok, in cytokinesis. By contrast, we failed to find evidence for a role for the Drosophila ortholog of Rok in cell division. We conclude that Citron plays an essential, non-redundant role in the Rho signalling pathway during Drosophila cytokinesis.